Occurrence of transient back pain among teachers, researchers and students in Kharkiv - Korzh, Mykola; Kotulskiy, Igor; Protsenko, Olena; Demyanenko, Ganna; Moskalenko, Natalya; Poklonskiy, Eugen; Salnikov, Vyacheslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
In modern medicine the problem of diagnosing and treatment of dorsal pain is one of the most relevant which is supported by the global statistics. Dorsal pain is included in list of diseases and pathological conditions (together with osteoporosis, osteoarthritis, rheumatoid arthritis, injuries of the musculoskeletal system) which has essential medical and social value and cause significant economic losses to society according to opinion of foreign experts. Purpose: to determine peculiarities of transitory dorsalgia manifestations in mental work individuals with theoretical analysis of possible pathophysiological mechanisms of this pain development. Methods: we conducted a questionnaire survey of 765 persons (age 21-70 years) in 3 scientific research and 7 educational institutions in Kharkiv. Results: an analysis of the completed questionnaires showed that in the evaluated sample women were predominant (401 / 55.39 %), and the same was in age group of young people up to 30 years (261 / 36.05 %). Transient dorsal pain was noted in 483 people (66.71 ± 1.75) %. Teachers have had recurrent dorsal pain significantly more often (p = 0.0001) than research staff and students. According to gender characteristics manifestations of dorsalgia were prevalent in women (p = 0.005). Statistically, tight correlation between transient manifestations of dorsalgia was detected with sleep disturbances and psycho emotional stresses. We have shown that dorsal pain was diagnosed in 57.22 % individuals whose work according to them was calm, and in 68.42% individuals who described their work as hard but without stresses, and in 74.50 % persons whose work is accompanied by psycho emotional stresses. Dorsal pain was noted in (56.25 ± 3.44) % persons who reported daily deep and prolonged (> 8 hours) sleeping. Among those with a deep but not long (<8 hours) sleeping pain was noted in (63.12 ± 2.78)% cases. If cases of not deep sleeping with bout of insomnia dorsal pain was noted in (79.77 ± 3.05)% of respondents. And finally, in the group of persons who have suffered from insomnia transitory dorsal pain was noted in (92.68 ± 4.07) % cases. In vast majority of people with transitory dorsal pain its manifestations did not have any seasonal dependence. The questionnaire identified the most common pain patterns: aching, burning, cutting, stitching, and patient’s own version. An analysis of the data showed that the vast majority of people (71.84 %) have had aching, 9.94 % - stabbing, 8.9 % - cutting, 6.63 % - burning, and 3.11% have had other type of pain. In fact pain spectrum was limited by these four types, and manifestations of dull pain primarily dominated. Conclusion: in-depth research of transitory dorsal pain pathogenesis and improvement of differential diagnostics of various forms of this disease is necessary. Obtained data represent an important basis for further study of transitory dorsal pain pathogenesis and for deepening of possibilities for differential diagnostics between spinal, neurogenic, immunogenic and other forms of dorsalgia.